Dinamika Anggota Kelompok Tani Matuari di Kelurahan Paniki Bawah Kecamatan Mapanget Kota Manado - Sembiring, Iren Sintia Br; Memah, Melsje Y.; Tambas, Jane Sulinda (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
The Matuari Farmer Group is a farmer group in Paniki Bawah Village, Mapanget District, Manado City, North Sulawesi Province, and is included in the intermediate level farmer group. This farmer group was founded by Mrs. Johana Lumanaw in 2015, until now it has been 8 years old consisting of women farmers consisting of 10 active farmer group members including the chairman, secretary, treasurer and members. The land area in the Matuari Farmer Group is 1 Ha. This study aims to determine the Dynamics of Matuari Farmer Group Members in Paniki Bawah Village, Mapanget District, Manado City, which is studied from elements of group dynamics. This research was carried out for three months, from May to July 2023 in Paniki Bawah Village, Mapanget District, Manado City. Data analysis applied in this study used qualitative descriptive analysis and Likert scale. The sampling method is Purposive Sampling. The research data collected are primary data and secondary data. The results of the research that became the purpose of conducting the Matuari Farmer Group Member Dynamics research in Paniki Bawah Village, Mapanget District, Manado City were Dynamic by obtaining a total overall score of 920 with a percentage of 92.92%.